Implementation of LiDAR Sensor for Mobile Robot Delivery Based on Robot Operating System - Fiqri Ahmad Agung; H Herizon; Era Madona; Muhammad Rohfadli; Ja'far Ja'far (Politeknik Negeri Padang, 2023)
Recent research has focused on the development of mobile delivery robots as part of the rapidly evolving autonomous technology. The main focus is on creating mobile robots capable of efficiently delivering goods without human intervention. This involves designing systems, core technologies, and overcoming various challenges. The navigation system of the delivery robot is enhanced by the use of LIDAR (Light Detection and Ranging) sensors. One of the sensors used is the RPLIDAR A1M8 which is capable of detecting nearby objects with a distance reading of 360°. Trials were conducted to evaluate the robot's navigation performance with a load variation of 0 kg to 20 kg. The test results show that RPLIDAR A1M8 can read distances up to 1200 cm with an error rate of about 3.15%, and a minimum distance of 15 cm with an error of 1.45%. The durability of this sensor reading is well maintained, with a presentation error of only 0.4%. Mapping trials in the room produced an average error of 18.57% without tracking, and 5.02% with tracking. The weight of the load carried by the robot affects the speed and travel time. The heavier the load, the robot speed decreases from 0.264 m/s at 0 kg load to 0.127 m/s at 20 kg load. Likewise, the travel time increases with the weight of the load, from 7.6 seconds to 15.6 seconds.